Advances in Whole‐Cell Photobiological Hydrogen Production. Issue 4 (1st February 2021) - Chen, Jie; Li, Qian; Wang, Lihua; Fan, Chunhai; Liu, Huajie
Abstract : Solar energy is the largest energy source on Earth. In contrast to the limited and greenhouse gases‐emitting fossil fuels, solar energy is inexhaustible, carbon neutral, and nonpolluting. The conversion of this most abundant but highly diffused source into hydrogen is increasingly attractive. In nature, photosynthetic microorganisms exploit solar energy to produce hydrogen via photosynthesis, which is also known as photobiological hydrogen production. More recently, various types of artificial materials have been developed to hybrid microorganisms for converting solar energy into hydrogen, namely, semiartificial photosynthesis hydrogen production. Herein, the strategies for converting solar energy into hydrogen with whole‐cell biocatalyst are summarized and their potentials for future social sustainable development are discussed. Abstract : The conversion of solar energy into hydrogen with whole‐cell biocatalyst is promising for solar energy utilization. Herein, two common ways for converting solar energy into hydrogen are summarized: one is using native or gene‐engineered cells as pure whole‐cell biocatalyst and the other one is using native or gene‐engineered cells combined with artificial materials as whole‐cell biocatalyst hybrids.